MEDICAL RECORD MANAGEMENT STANDARDS ASSESSMENT AT MARANATHA DENTAL AND MOUTH HOSPITAL (DMH) - Dhaifullah Shidqi Akbarsyah; Iqbal Santosa Iqbal Santosa; Widyatasya A Nutrisha (JIKO (Jurnal Informatika dan Komputer), 2022)
Medical record management is an effort to maintain and manage medical record documents, both conventionally (paper-based) and electronically at each hospital health service facility. The author conducted field observations of the Maranatha Dental and Oral Hospital (RSGM) which were carried out directly through semi-structured interviews with RSGM Maranatha regarding the current state of the medical record management unit. This study was structured to determine the state of the medical record management of RSGM Maranatha and provide solutions to problems related to compliance with the National Hospital Accreditation Standards (SNARS) and Joint Commission International (JCI). The author implements Phases 1 – 5 of COBIT 2019 as a reference framework in this research, the limits of the standards used are SNARS MIRM (Management of Information and Medical Records) 8 – 15 and JCI 4th and 5th Edition. This research is expected to provide relevant suggestions so that it can be a benchmark for hospitals in carrying out the medical record management process.